Relocation Dilemma: Social and Cultural Challenges in the Relocation of the Victims of Mount Rokatenda Disaster - Humaedi, Muhammad Alie (Universitas Negeri Semarang, 2016)
Mount Rokatenda has erupted several times, and brought about impacts on people in Palue Island, Sikka regency, East Nusa Tenggara. Since 1980, various attempts of disaster management through relocation have been carried out by the government, church, and non-governmental organizations. Unfortunately, the efforts to relocate the victims mainly fail because they always return to Palue Island. The threats of Mount Rokatenda and its vulnerability do not seemingly inhibit them to continue their lives there. This is evident in relocation attempt post-eruption in 2012-2013. The question is, how could the social and cultural aspects of Rokatenda victims hinder the relocation program? This ethnographic qualitative research which is done through in-depth interview and observation in April to May 2014 demonstrate that disaster events could also be cultural events. The emic aspect of the victims influence disaster management attempts, especially in the relocation program to the Besar Island. There is a feeling of secure and a sense of security from the ancestors, a view of prosperity for those who stay, and a strong value system that Palue Island is the place of birth, life and death has strongly bound the mythology and cosmology relationship of Palue people with their land. A re-interpretation of emic values through involving local traditional leaders is a strategic step towards the success of Rokatenda relocation program.